A pilot interventional study to evaluate the impact of cholecalciferol treatment on HbA1c in type 1 diabetes (T1D). Issue 4 (May 2017) - Perchard, R; Magee, L; Whatmore, A; Ivison, F; Murray, P; Stevens, A; Mughal, M Z; Ehtisham, S; Campbell, J; Ainsworth, S; Marshall, M; Bone, M; et al.
Abstract : Background: Higher 25(OH)D3 levels are associated with lower HbA1c, but there are limited UK interventional trials assessing the effect of cholecalciferol on HbA1c. Aims: (1) To assess the baseline 25(OH)D3 status in a Manchester cohort of children with type 1 diabetes (T1D). (2) To determine the effect of cholecalciferol administration on HbA1c. Methods: Children with T1D attending routine clinic appointments over three months in late winter/early spring had blood samples taken with consent. Participants with a 25(OH)D3 level <50 nmol/L were treated with a one-off cholecalciferol dose of 100, 000 (2–10 years) or 160, 000 (>10 years) units. HbA1c levels before and after treatment were recorded. Results: Vitamin D levels were obtained from 51 children. 35 were Caucasian, 11 South Asian and 5 from other ethnic groups. 42 were vitamin D deficient, but 2 were excluded from the analysis. All South Asian children were vitamin D deficient, with mean 25(OH)D3 of 28 nmol/L. In Caucasians, there was a negative relationship between baseline 25(OH)D3 level and HbA1c ( r  = −0.484, P  < 0.01). In treated participants, there was no significant difference in mean HbA1c at 3 months ( t  = 1.010, P  = 0.328) or at 1 year ( t  = −1.173, P  = 0.248) before and after treatment. One-way ANCOVA, controlling for age, gender, ethnicity, BMI and diabetes duration showed no difference in Δ HbA1c level. Conclusion: We report important findings at baseline, but in children treated with a stat dose of cholecalciferol, there was no effect on HbA1c. Further studies with larger sample sizes and using maintenance therapy are required.